Arthroscopic Bankart Repair Versus Open Bristow-Latarjet for Shoulder Instability: A Matched-Pair Multicenter Study Focused on Return to Sport. (December 2016) - Blonna, Davide; Bellato, Enrico; Caranzano, Francesco; Assom, Marco; Rossi, Roberto; Castoldi, Filippo
Background: The arthroscopic Bankart repair and open Bristow-Latarjet procedure are the 2 most commonly used techniques to treat recurrent shoulder instability. Purpose: To compare in a case control–matched manner the 2 techniques, with particular emphasis on return to sport after surgery. Study Design: Cohort study; Level of evidence, 3. Methods: A study was conducted in 2 hospitals matching 60 patients with posttraumatic recurrent anterior shoulder instability with a minimum follow-up of 2 years (30 patients treated with arthroscopic Bankart procedure and 30 treated with open Bristow-Latarjet procedure). Patients with severe glenoid bone loss and revision surgeries were excluded. In one hospital, patients were treated with arthroscopic Bankart repair using anchors; in the other, patients underwent the Bristow-Latarjet procedure. Patients were matched according to age at surgery, type and level of sport practiced before shoulder instability (Degree of Shoulder Involvement in Sports [DOSIS] scale), and number of dislocations. The primary outcomes were return to sport (Subjective Patient Outcome for Return to Sports [SPORTS] score), rate of recurrent instability, Oxford Shoulder Instability Score (OSIS), Subjective Shoulder Value (SSV), Western Ontario Shoulder Instability Index (WOSI), and range of motion (ROM). Results: After a mean follow-up of 5.3 years (range, 2-9 years), patients who underwent arthroscopic Bankart repair obtained better results in terms of return to sport (SPORTS score: 8 vs 6; P = .02) and ROM in the throwing position (86° vs 79°; P = .01), and they reported better subjective perception of the shoulder (SSV: 86% vs 75%; P = .02). No differences were detectable using the OSIS or WOSI. The rate of recurrent instability was not statistically different between the 2 groups (Bankart repair 10% vs Bristow-Latarjet 0%; P = .25), although the study may have been underpowered to detect a clinically important difference in this parameter. The multiple regression analysis showed that the independent variables associated with return to sport were preoperative DOSIS scale, type of surgery, and recurrent dislocations after surgery. Patients who played sports with high upper extremity involvement (eg, swimming, rugby, martial arts) at a competitive level (DOSIS scale 9 or 10) had a lower level of return to sport with both repair techniques. Conclusion: Arthroscopic stabilization using anchors provided better return to sport and subjective perception of the shoulder compared with the open Bristow-Latarjet procedure in the population studied. Recurrence may be higher in the arthroscopic Bankart group; further study is needed on this point.